An unsteady RANS study of thermal striping in a T-junction with sodium streams mixing at different temperatures - Duan, Jinping; Huang, Xiaoxue (Frontiers in Energy Research, 2023)
Thermal striping in a T-junction with sodium streams mixing at different temperatures is studied using unsteady Reynolds-averaged simulation (RANS). Different parameters including the momentum ratio of the streams (0.2–4.3), the temperature difference between the streams (15–35 K), and the bulk Reynolds number (5,000–9,000) are investigated. Simulation results demonstrate that the flow pattern is mainly determined by the momentum ratio, while the temperature difference and the bulk Reynolds number have little influence within the range considered. The location of the separation point of the recirculation zone increases with the momentum ratio while the location of the thermal front decreases with it. In addition, the sensitivity of the temperature fluctuations to a range of low-Reynolds-number turbulence models are studied, which demonstrate that the time-varying temperature fluctuations predicted by these turbulence models are significantly smaller than the experimental measurements. High-fidelity simulations which fully resolve the temperature fluctuations will be carried out as the future work to complement the statistics of the temperature fluctuation.